The Impact of War as an Exceptional Incident on Employment Contracts - Nedal Jamal M. Jarada (International Journal of Law Research and Studies, 2026)
On October 7th, 2023, Israel launched a brutal war on the Gaza Strip. It affected people, structures, animals, and most aspects of life were disrupted, which lead to paralysis of the labor force and make it unable to work. As a result, universities, societies, and institutions were closed, agriculture, transportation, and contracting were disrupted, production stopped in factories, labor become unemployed, and labor contracts became threatened in a way that not less dangerous from their workplace. These are inevitable consequences of the war as an exceptional incident that occurred in the labor contracts, and have various legal effects cast a shadow on employment contracts. In the light of the legal theories constructed by legal thought and regulated by civil law, and the legal effects resulting from it, and directing the war to its legal destination, and acknowledging the extent to which it is considered force majeure or an exceptional incident, and explaining the impact resulting from the inability to implement the obligations generated about the employment contract because of the war, the adequacy of the Palestinian labor law which is compared by legislative regulation to address exceptional emergency incidents that occur in employment contracts, and how the law deals with employer exploiting of this war to terminate some employment contracts.
Keywords: War; Exceptional Incident; Employment Contracts; Inability; Force Majeure